Design and Construction of a Web-Based MSME E-Marketplace Application Using the Agile Method (Case Study: Kepanjenlor Village, Blitar City) - Jannah, Ayu Roudhotul; Putra, Agung Brastama; Wibowo, Nur Cahyo (Holistic Science, 2025)
MSMEs play a vital role in the local economy, yet many MSMEs in Kepanjenlor Village, Blitar City, have not utilized digital technology for product promotion and sales. This study aims to design and build a web-based e-marketplace application to support online product marketing. The approach used is the Agile method with iterative stages: planning, design, development, testing, deployment, and review. System data was obtained through observation and interviews, with design using UML and Figma, implementation using Laravel, and testing using the Black Box Testing method achieving an accuracy score of 92%. The result is an e-marketplace application that supports registration, login, product catalog, ordering, and MSME data management features. This application has been tested and received a positive response, and is considered capable of meeting the digitalization needs of MSMEs in Kepanjenlor Village, Blitar City.